1997
DOI: 10.1111/j.1558-5646.1997.tb01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Population Genetic Structure in Tropical Pacific Sea Urchins

Abstract: Abstract.-Unlike populations of many terrestrial species, marine populations often are not separated by obvious, permanent barriers to gene flow. When species have high dispersal potential and few barriers to gene flow, allopatric divergence is slow. Nevertheless, many marine species are of recent origin, even in taxa with high dispersal potential. To understand the relationship between genetic structure and recent species formation in high dispersal taxa, we examined population genetic structure among four sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 44 publications
4
158
1
1
Order By: Relevance
“…This suggests that the significant effect of IBD across the species range was a result of complete isolation of the WIO populations rather than a gradual dilution of settlement events with increasing geographical distance. This pattern is similar to that found among pelagic larval dispersing marine organisms, which generally show signs of IBD only at the largest spatial scales (Richardson 1983;Palumbi et al 1997;Planes and Fauvelot 2002).…”
Section: Genetic Structure Among Oceanssupporting
confidence: 62%
“…This suggests that the significant effect of IBD across the species range was a result of complete isolation of the WIO populations rather than a gradual dilution of settlement events with increasing geographical distance. This pattern is similar to that found among pelagic larval dispersing marine organisms, which generally show signs of IBD only at the largest spatial scales (Richardson 1983;Palumbi et al 1997;Planes and Fauvelot 2002).…”
Section: Genetic Structure Among Oceanssupporting
confidence: 62%
“…Genetic structure or divergence across the large expanses of open water (B2000 km) that lie between archipelagos in the Western and Central Pacific, such as what we found in N. canalis, is commonly observed in marine species (Palumbi et al, 1997;Bernardi et al, 2001;Lessios et al, 2001;Crandall et al, 2008) as well as in an amphidromous goby (Keith et al, 2005). It is therefore remarkable that N. dilatatus shows no evidence of genetic structure across this span.…”
Section: Multiple Colonizations Of the Central Pacificmentioning
confidence: 57%
“…seagrass: Bandeira & Nilsson 2001;bryozoans: Goldson et al 2001;fish: Rocha-Olivares & Vetter 1999), other studies have found no correlation (echinoderms: Palumbi et al 1997;reef fishes: Shulman & Bermingham 1995). In this study, 2 major reasons may explain the absence of current/gene flow correlation of Laminaria digitata in the English Channel.…”
Section: Genetic Structure and Current Patternsmentioning
confidence: 99%